A Resource-Based and Dynamic Capabilities Perspective on Batik SME Performance: The Sequential Mediating Roles of Digital Marketing and Innovation Capability - Intan Muliana Rhamdhani; Sulis Riptiono (Department of Business and Entrepreneurship, Faculty of Economics and Business, Universitas Negeri Makassar, 2026)
This study investigates the relationships between entrepreneurial capability, Digital Marketing Capability (DMC), Innovation Capability (IC), and Business Performance (BP) in batik SMEs. Based on the Resource-Based View (RBV) and Dynamic Capabilities Theory (DCT), it proposes a serial mediation model in which DMC and IC elucidate the link among EC and business performance. A quantitative cross-sectional survey was conducted among owners of batik SMEs in Central Java, Indonesia. Using purposive sampling, 380 valid responses were collected and analyzed using Structural Equation Modeling (SEM-AMOS). The proposed mediation effects were evaluated using a bootstrapping procedure. The results reveals that EC is positively associated with DMC, IC, and BP. DMC and IC are also positively effects with business performance. Bootstrapping results support the sequential mediating roles of DMC and IC in linking EC to business performance. This study extends RBV and DCT by empirically validating a serial mediation model that explains how EC is translated into BP through the sequential development of DMC and IC. The findings provide new evidence from batik SMEs in Indonesia, an underexplored context in the capability and digital marketing literature.